Piriformis Fossa – An Anatomical and Orthopedics Consideration - O.P. Lakhwani; P.S. Mittal; D.C. Naik (Journal of Clinical and Diagnostic Research, 2014)
Introduction: Piriformis fossa is an important anatomical landmark having significant clinical value in orthopedic surgery; but its location and anatomical relationship with surrounding structures are not clearly defined. Hence it is necessary to clearly describe it in respect to anatomical and orthopedic aspect. Materials and Methods: Fifty Cadaveric dry femoral bones and Dissection of the four hip specimens were used to study the Piriformis fossa in respect to location and its relationship with surrounding structures. Clinical importance of piriformis fossa was determined in reference to antegrade femoral nail insertion. Observations: Piriformis muscle and so called piriformis fossa are unrelated entities. Piriformis fossa is anatomical site of insertion of obturator externus. In dry cadaveric femora; fossa was not always located in the direction of femoral shaft. It was located in the direction of femoral shaft in 24% cases only. In 68% cases femoral canal was aligned lateral and in 8% cases, it lies medial to the fossa. Conclusion: Piriformis fossa should be named as Trorchanteric fossa or Obturator fossa for better anatomical description. So called Piriformis fossa does not found to be universally corresponding to femoral shaft hence selection of entry site should be based on variable proximal femur and area on femur which corresponds to femoral shaft.